Prenatal seasonality, child growth, and schooling investments: Evidence from rural Indonesia - Yamauchi, Futoshi (International Food Policy Research Institute, 2011)
This paper examines the impacts of prenatal conditions on child growth using recent data from Indonesia. There is seasonality in birth weight: this measure is significantly higher during the dry season than during the rainy season. The empirical results show that an increase in birth weight improves child growth outcomes as measured by the height and weight Z-scores, as well as schooling performance as measured by age at start of schooling and number of grades repeated. The interactions of ecological variations affect early childhood human capital formation and can have long-term impacts on children's outcomes.